2015
DOI: 10.1021/acsami.5b09993
|View full text |Cite
|
Sign up to set email alerts
|

UV Light-Induced Generation of Reactive Oxygen Species and Antimicrobial Properties of Cellulose Fabric Modified by 3,3′,4,4′-Benzophenone Tetracarboxylic Acid

Abstract: 3,3',4,4'-Benzophenone tetracarboxylic acid (BPTCA) could directly react with hydroxyl groups on cellulose to form ester bonds. The modified cotton fabrics not only provided good wrinkle-free and ultraviolet (UV) protective functions, but also exhibited important photochemical properties such as producing reactive oxygen species (ROS) including hydroxyl radicals (HO(•)) and hydrogen peroxide (H2O2) under UV light exposure. The amounts of the produced hydroxyl radical and hydrogen peroxide were measured, and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Having shown that UV irradiation can accelerate polymerization of the phenolic compounds, additional experiments were performed in order to investigate the mechanistic aspects of the UV‐induced transformation. It is known that reactive oxygen species (ROS), including singlet oxygen ( 1 O 2 ), superoxide radicals (O 2 −• ), or highly reactive hydroxyl radicals (•OH) can be generated under UV irradiation even in the presence of traces of O 2 . Previously, we reported the importance of ROS in the case of UV‐induced dopamine polymerization .…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that UV irradiation can accelerate polymerization of the phenolic compounds, additional experiments were performed in order to investigate the mechanistic aspects of the UV‐induced transformation. It is known that reactive oxygen species (ROS), including singlet oxygen ( 1 O 2 ), superoxide radicals (O 2 −• ), or highly reactive hydroxyl radicals (•OH) can be generated under UV irradiation even in the presence of traces of O 2 . Previously, we reported the importance of ROS in the case of UV‐induced dopamine polymerization .…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 produced over composite membranes was quantified by the method reported by Hou et al and another indirect spectrophotometric method detailed in the Standard Operating Procedure: Procedure for Analyzing Hydrogen Peroxide Concentrations in Water (Procedure No: GSI/SOP/BS/RA/C/7, Issue Date: June 15, 2009) [14] . A 5-mg membrane sample was placed in deionized water (5 mL) and exposed to daylight or dark conditions for a certain time.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, BPTCA aqueous solutions can be directly used in fiber membrane processing and react with hydroxyl groups in the presence of sodium hypophosphite as a catalyst to form esters [11] , [13] . The ability of BPTA to promote ROS (e.g., HO⋅ and H 2 O 2 ) generation both upon irradiation with light and under dim light/dark conditions results in “always-on” bactericidal activity, as the thus produced ROS rapidly destroy DNA, RNA, proteins, and lipids to induce bacterial death and virus inactivation [11] , [14] . Polymer nanocomposites are superior functional materials comprising nanoparticles coated on a polymer matrix or dispersed therein [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment should be durable to washing, dry cleaning, hot pressing and compatible with textile chemical finishing processes such as dyeing and also it has to be cost effective 13 . A number of chemicals such as, benzophenone, organometallics, iodophors (substances that slowly release iodine), phenols and thiophenols, metallic salts, antibiotics, heterocyclics with anionic groups, nitro compounds, ureas and related compounds, formaldehyde derivatives and amines [14][15][16] have been employed to impart antimicrobial activity to textiles. Many of these chemicals, however, are toxic to humans and do not easily degrade in the environment.…”
Section: Introductionmentioning
confidence: 99%